HETEROSIS DAN DAYA GABUNG PADA PERSILANGAN HALF DIALLEL CABAI BESAR DAN CABAI KERITING (Capsicum annuum L.) - Yesy Mardianawati; Muhamad Syukur (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2016)
The aim of this research was to study estimation the heterosis and heterobeltiosis of fifteen hybrids,the general combining ability (GCA), and the specific combining ability (SCA) of six chili inbred lines of hybridization between big and curly pepper (Capsicum annuum L.). This research was conducted at Genetic and Plant Breeding Laboratory and IPB Experimental Field, Leuwikopo, Dramaga, Bogor, from September 2012 to March 2013. The experimental design used was randomized complete block design (RCBD) single factor with three replication. Plant materials were six chili indred lines, fifteen hyrids from hybridizaion half diallel crosses, and two commercial hybrid. Genotype IPB C5 showed the highest GCA for harvesting time, fruit weight, and yield. Genotype IPB C120 showed the highest GCA for plant heigh and fruit length. Genotype IPB C159 x IPB C111, IPB C159 x IPB C2, IPB C120 x IPB C5, IPB C111 x IPBC2, and IPB C19 x IPB C5 had positive heterosis, heterobeltiosis, and SCA values for some variables observed. All these genotypes had advantages that were not significantly different from the comparison of varieties TM 999 and Princeess on all characters observed.